Making time for literacy: teacher knowledge and time allocation in instructional planning - Spear-Swerling, Louise; Zibulsky, Jamie (Reading and Writing, 2014)
This study examined how K-5 general and special educators (N = 102) would choose to allocate time in a 2-h language arts block if they could do so as they wished, and how these choices related to their knowledge base for reading instruction. Preferences for time allocation were assessed through an open grid on which participants listed descriptions of planned instructional activities and amount of time for each activity; teacher knowledge was assessed via a multiple-choice measure involving questions about assessment and instruction in the five components of reading. Results showed that many teachers planned little or no time for areas such as assessment, vocabulary, phonemic awareness, and spelling; also, relatively little time was devoted to basic writing skills and virtually none to writing processes such as planning or revision. There were few significant differences between general and special educators in time allocation on the grid, although there were more differences by grade level (e.g., grids for Grades K-1 vs. Grades 4-5). Teacher knowledge did predict teachers' time allocation plans, particularly for teachers with relatively high knowledge of phonemic awareness and phonics. Overall, however, many teachers chose to allocate time in ways inconsistent with scientific recommendations, in writing as well as in reading. The study highlights the importance of research-based, targeted teacher professional development in literacy, as well as the need for schools to provide comprehensive, research-based core reading and writing curricula to educators, with attention to fidelity of implementation.
Keywords: Literacy; Reading; Reading instruction; Teacher beliefs; Teacher knowledge; Writing instruction; dept.sed; peer-reviewed